Study on Economic Census and Budget Planning of Haryana: Analysis of Economic Census and Budget Planning in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Consumption Expenditure of the Government is estimated atRs. 1459026 lakh in 2011-12 (B.E.) as against Rs. 1456753 lakh in 2010-11(R.E.) and Rs. 1170360 lakh in 2009-10. The consumption expenditure of theGovt. is estimated to increase by 0.16 percent in 2011-12 (B.E.) over 2010-11(R.E.) whereas it increases by 24.47 percent in 2010-11 (R.E.) over 2009-10. Gross Capital Formation i.e. investment on buildings,roads & other constructions, purchase of vehicles and machinery &equipment by Administrative Departments and Departmental CommercialUndertakings is estimated at Rs. 425441 lakh in 2011-12 (B.E.) as against Rs.374245 lakh in 2010-11 (R.E.) and Rs.357125 lakh in 2009-10 showing an increaseof 13.68 percent in 2011-12 (B.E.) over 2010-11 (R.E.) where as it increased by4.79 percent in 2010-11 (R.E.) over 2009-10. Current transfers which also include subsidies and interestpayments are estimated at Rs. 1484599 lakh in 2011-12 (B.E.) as against Rs.1312149 lakh in 2010-11 (R.E.) and Rs. 1013508 lakh in 2009-10. It indicatesthat current transfers are likely to increase by 13.14 percent in 2011-12(B.E.) over 2010-11 (R.E.) whereas this increase was 29.47 percent in 2010-11(R.E.) over 2009-10.